Cathodoluminescence imaging of cellular structures labeled with luminescent iridium or rhenium complexes at cryogenic temperatures - Vancová, Marie; Skoupý, Radim; Ďurinová, Eva; Bílý, Tomáš; Nebesářová, Jana; Krzyžánek, Vladislav; Kolouch, Aleš; Horodyský, Petr (Scientific reports, 2022)
We report for the first time the use of two live-cell imaging agents from the group of luminescent transition metal complexes (IRAZOLVE-MITO and REZOLVE-ER) as cathodoluminescent probes. This first experimental demonstration shows the application of both probes for the identification of cellular structures at the nanoscale and near the native state directly in the cryo-scanning electron microscope. This approach can potentially be applied to correlative and multimodal approaches and used to target specific regions within vitrified samples at low electron beam energies.
Keywords: Luminescence; Rhenium; teplota; rhenium; Temperature; luminiscence; Iridium; Coordination Complexes; komplexní sloučeniny; iridium